High-strength medium-entropy alloy with nanoscale relaxor grain boundary and preparation method of high-strength medium-entropy alloy
By rolling and annealing in medium and high entropy alloys, combined with low temperature and short-term grain boundary relaxation treatment, the problems of low alloy strength and complex process are solved, and high-strength and low-cost industrial production are achieved.
Patent Information
- Application Number
- CN202411734920.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-04
AI Technical Summary
Medium and high entropy alloys are usually low in strength in industrial production, and are prone to casting defects, difficult to meet the use requirements of specific occasions, and the existing technology processes are complex, which increases production costs.
Through rolling and appropriate annealing treatment, the grain size and dislocation configuration in the alloy are adjusted, and grain boundary relaxation treatment is adopted for low temperature and short-term time to eliminate excessive dislocations at the grain boundary, so as to transform the grain boundary into a low-energy state, thereby improving the strength of the alloy.
It significantly improves the tensile strength of the medium-entropy alloy, breaks through the inverted relationship between strength and plasticity, simplifies the preparation process, reduces the energy consumption cost, and makes it suitable for industrial mass production.
Smart Images

Figure CN119753534A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medium-entropy alloys, and in particular to a high-strength medium-entropy alloy with nanoscale relaxed grain boundaries and a preparation method thereof. Background Art
[0002] In recent years, medium and high entropy alloys have attracted widespread attention due to their large composition design space and excellent comprehensive performance. The high entropy effect at the thermodynamic level can effectively inhibit the formation of brittle intermetallic compounds, the lattice distortion effect at the crystal structure level significantly improves the material strength, the hysteresis diffusion effect at the kinetic level gives the alloy good thermal stability, and the "cocktail" effect at the performance level makes the material exhibit excellent comprehensive performance. However, in the industrial production process, the strength of the casting alloy is usually low, and it is often accompanied by defects such as pores, inclusions, shrinkage cavities, and its mechanical properties cannot meet the use requirements of specific occasions. Studies have found that through severe plastic deformation treatments such as rolling, forging, stamping, extrusion, and drawing, casting defects can be effectively eliminated; and the grains are refined during the deformation process, and a high-density dislocation structure is introduced, which can significantly improve the overall strength of the material. Annealing treatments at different temperatures and times based on severe plastic deformation treatments can regulate the interface structure and defect state in the alloy, and further adjust the mechanical properties of the alloy. However, the improvement of material plasticity is inevitably accompanied by a decrease in strength. How to break the inverted relationship between strength and plasticity has always been a key issue that researchers have been committed to solving.
[0003] The patent with application number 202311300326.1 discloses a method for preparing a medium-entropy alloy of VCoNi with high strength and high plasticity at low temperature, including: using V, Co, and Ni to mix according to a predetermined mass percentage and put them into a crucible in order, repeatedly melting and cooling to obtain a medium-entropy alloy material; subjecting the obtained medium-entropy alloy material to a solid solution treatment under a vacuum environment, and then processing it to the initial plate thickness by hot forging to obtain a plate; subjecting the hot forged plate to high-temperature rolling in different directions, and then rolling processing to obtain a predetermined reduction, and then mechanically grinding and decontamination treatment of its surface to obtain a high-entropy alloy material; subjecting the obtained high-entropy alloy material to an ordered annealing treatment and a cooling treatment at a predetermined cooling rate, and finally obtaining a multi-level heterogeneous medium-entropy alloy material. However, this technical method requires low-temperature cold rolling and a high cooling rate, and there are problems such as complex process flow and increased production costs, which limit actual production and application.
[0004] The patent application number 201910885613.0 discloses a high-strength, high-plasticity, wear-resistant, high-entropy alloy and its preparation method. By sequentially casting, homogenizing, hot rolling and annealing the alloy melt, a high-strength, high-plasticity, wear-resistant, high-entropy alloy with a tensile yield strength of 1130MPa, a tensile strength of 1380MPa, and an elongation of 92% is obtained; the wear resistance at room temperature reaches 80% of that of M2 high-speed steel. However, the number of alloy elements in this patented technology is large, and a variety of complex intermetallic compounds may be formed inside the material. The microstructure is difficult to predict and control, which brings challenges to the performance evaluation of the material and subsequent processing and manufacturing.
[0005] The patent with application number 201910232105.2 discloses a method for preparing a medium-entropy alloy with a tensile strength of 1.5GPa, the steps of which include: selecting a CoCrNi ternary medium-entropy alloy as a blank, heating and rolling the blank into a 4-12mm plate, and then air-cooling it to room temperature; heating the air-cooled plate in a heating furnace, keeping it warm, and then quenching it to room temperature, and then cold-rolling it at a temperature of -50°C, and finally heating the cold-rolled plate in an annealing furnace, keeping it warm, and then quenching it to room temperature to obtain a medium-entropy alloy with a tensile strength of 1.5GPa. Although the patent obtains a medium-entropy alloy with high strength and high plasticity through hot rolling, annealing, cold rolling, and re-annealing. However, the patented technology involves cold rolling and multiple quenching treatments at -50°C, the process flow is complicated, and factors such as the cooling medium, cooling rate, and workpiece shape directly affect the quenching effect, and the entire process requires precise control.
[0006] In summary, exploring simple, efficient, low-cost and easy-to-implement methods for optimizing the performance of medium and high entropy alloys is an important research direction to broaden the engineering application prospects of medium and high entropy alloys. Summary of the invention
[0007] Based on this, the purpose of the present invention is to provide a high-strength medium-entropy alloy with nanoscale relaxed grain boundaries and a preparation method thereof, and to effectively adjust the grain size and dislocation configuration in the alloy through rolling and appropriate annealing to obtain a high-strength medium-entropy alloy with nanoscale relaxed grain boundaries, thereby breaking through the inverted relationship between alloy strength and plasticity, simplifying the preparation process, and reducing energy consumption costs, making it suitable for industrial mass production.
[0008] The present invention is specifically achieved through the following technical solutions:
[0009] A high-strength medium-entropy alloy with nanoscale relaxed grain boundaries, the structural formula of which is Co x Cr y Ni z -M a -N b , wherein x, y, z, a, and b are all atomic percentages, and x+y+z+a+b=100%.
[0010] Furthermore, x=25-35%, y=25-35%, z=25-35%, Co, Cr and Ni are used as main constituent elements, the components are simple, the physical and chemical properties of the alloy are relatively stable, and it is easy to control and optimize.
[0011] Furthermore, M and N can be the same or different and can be selected from C, P, O or N. M and N as added elements can affect the grain boundary bonding strength of the alloy to a certain extent and improve the strength of the alloy.
[0012] A method for preparing a high-strength medium-entropy alloy with nanoscale relaxed grain boundaries comprises the following steps:
[0013] S1, smelting: weigh raw materials according to proportion, mix them evenly, and then smelt them under argon protection to obtain an ingot;
[0014] S2, hot rolling: the ingot is homogenized, then hot rolled to obtain a hot-rolled plate, and then cooled to room temperature;
[0015] S3, annealing and cold rolling: annealing the hot-rolled sheet and then cold-rolling it at room temperature to obtain a cold-rolled sheet;
[0016] S4, grain boundary relaxation: the cold rolled sheet is heated to 500-600°C for grain boundary relaxation treatment for 15-60 min. After the grain boundary relaxation treatment, the sheet is air-cooled to room temperature to obtain a high-strength medium-entropy alloy.
[0017] The present invention can maintain the grains at a suitable size by performing grain boundary relaxation treatment on the cold-rolled sheet at a relatively low temperature, and the grain boundaries tend to change to a low energy state during the plastic deformation process, so that the grain boundaries are not easy to move at high temperatures, so as to eliminate excessive grain boundary dislocations and reduce the nucleation sites of dislocation sources. At the same time, the smaller the grain size, the lower the grain boundary energy, thereby reducing the driving force of recrystallization.
[0018] Compared with the traditional high temperature annealing treatment, the recrystallized grains grow significantly, and the fine grain strengthening in the alloy gradually weakens, which is manifested as a decrease in the strength of the alloy. The present invention adopts grain boundary relaxation treatment. Due to the reduction in the number of dislocation sources, the critical shear stress required for dislocation movement increases, which is manifested as an increase in the strength of the alloy.
[0019] In addition, the preparation method of the present invention is simple and efficient, and can be easily implemented based on the existing plate rolling production process, avoiding dependence on precision equipment and complex processes, and is conducive to large-scale application in industrial production.
[0020] Furthermore, in step S1, a corresponding amount of alloy raw materials with a purity of ≥99.9% are weighed, the raw materials are ultrasonically cleaned in anhydrous ethanol to remove impurities on the surface of the raw materials, and mixed smelting is performed after drying.
[0021] The specific smelting steps are: after mixing the alloy raw materials evenly, put them into an induction melting furnace, and melt them under argon protection, the melting temperature is 1500-1700°C, the heating rate is 100-400°C / min, and the insulation time after the raw materials are melted is 10-30min; after insulation, the molten metal is poured into a mold to form an ingot.
[0022] Furthermore, in step S2, the hot rolling treatment adopts a hot charging method, the ingot at room temperature is heated to a hot rolling temperature of 1100±50°C, the heating rate is 100-300°C / min, the holding time is 15-30min, the rolling deformation per pass is 5%-10%, and the total hot rolling deformation is 20%-40%; the final rolling temperature is 900-1100°C, and a hot-rolled plate with a thickness of 7-10 mm is obtained; after hot rolling, it is air-cooled to room temperature.
[0023] Preferably, the thickness of the hot-rolled plate is 8 mm.
[0024] Furthermore, in step S2, the specific steps of the homogenization treatment are: placing the ingot in an annealing furnace at 1150±50°C for 200-240 minutes, taking it out and air-cooling it to room temperature.
[0025] Furthermore, in step S3, the annealing treatment temperature is 1150±50°C, the heating rate is 5-15°C / min, the holding time is 5-30min, and after the holding is completed, the annealing treatment is air-cooled to room temperature.
[0026] Furthermore, in step S3, the cold rolling process has a single rolling deformation of 2% to 5%, a total rolling deformation of 80% to 85%, and a plate with a thickness of 1.0 to 1.5 mm is obtained.
[0027] Preferably, the thickness of the cold-rolled sheet is 1.2 mm.
[0028] Furthermore, the matrix structure of the prepared high-strength medium-entropy alloy is a dislocation cell with a size of 100 to 500 nm, and there are no obvious crystal defects such as dislocations and stacking faults in the dislocation cells.
[0029] Furthermore, the tensile strength of the high-strength medium-entropy alloy is 1.6 to 1.9 GPa, which is significantly higher than the tensile strength of the alloy obtained by traditional high-temperature annealing treatment. Compared with the traditional high-temperature heat treatment method, the present invention can significantly improve the strength of the material through low-temperature and short-time grain boundary relaxation treatment, and has high economic benefits and application prospects.
[0030] The beneficial effects of the present invention are:
[0031] (1) Provide a Co x Cr y Ni z -M a -N b Multi-element system, with Co, Cr, and Ni as the main components, simple components, relatively stable physical and chemical properties of the alloy, easy to control and optimize, C, P, O or N, M and N as added elements, can affect the grain boundary bonding strength of the alloy to a certain extent, and can prepare high-strength medium-entropy alloys with nanoscale relaxed grain boundaries, and the tensile strength of the alloy is 1.6-1.9GPa;
[0032] (2) Provide a method for preparing a high-strength medium-entropy alloy, which has a simple and efficient process flow and can be easily implemented based on the existing plate rolling production process, avoiding dependence on precision equipment and complex processes, and is conducive to large-scale application in industrial production;
[0033] (3) By performing grain boundary relaxation treatment at a lower temperature, the excessive dislocations introduced by cold rolling at the grain boundary are eliminated, and the grain boundary is transformed into a low-energy state. As the number of dislocation sources decreases, the critical shear stress required for dislocation movement increases, which is manifested as an increase in alloy strength.
[0034] (4) Based on the cold rolling process widely used in industrial production, the strength of the material can be significantly improved through low-temperature and short-term grain boundary relaxation treatment, which can reduce energy consumption and production costs, and has high economic benefits and application prospects.
[0035] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The engineering stress-strain curve of the medium entropy alloy prepared in Example 1 before and after grain boundary relaxation;
[0037] Figure 2 This is a microscopic image of the organizational structure of the medium entropy alloy in Example 1 before grain boundary relaxation treatment;
[0038] Figure 3 This is a microscopic image of the organizational structure of the medium entropy alloy after grain boundary relaxation in Example 1;
[0039] Figure 4 This is the engineering stress-strain curve of the medium-entropy alloy prepared in Comparative Example 5. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] Use a balance to weigh the corresponding amount of Co, Cr, and Ni raw materials with an equal atomic ratio and a purity of ≥99.9%, perform ultrasonic cleaning on the raw materials in anhydrous ethanol to remove impurities on the surface of the raw materials, and then dry them for later use.
[0043] The alloy raw materials are mixed evenly and put into an induction melting furnace for melting under argon protection. The melting temperature is 1600±100°C, the heating rate is 300±100°C / min, and the insulation time after the raw materials are melted is 15 minutes. After insulation, the molten metal is poured into a mold to form an ingot.
[0044] The ingot was placed in an annealing furnace at 1150°C for 240 minutes, and then air-cooled to room temperature. Then, the ingot at room temperature was heated to a hot rolling temperature of 1100°C by hot charging, with a heating rate of 200±100°C / min, a holding time of 15 minutes, a rolling deformation of 5% per pass, a total hot rolling deformation of about 40%, and a final rolling temperature of 1000±100°C to obtain a hot-rolled plate with a thickness of 8 mm; after hot rolling, it was air-cooled to room temperature.
[0045] The hot-rolled plate was annealed at 1150°C, with a heating rate of 10°C / min and a holding time of 10min. After the holding time, the plate was air-cooled to room temperature. The annealed plate was cold-rolled at room temperature, with a single rolling deformation of 2% and a total rolling deformation of 85%, to obtain a plate with a thickness of 1.2 mm.
[0046] The cold-rolled sheet was post-treated (i.e., grain boundary relaxation treatment) at 500°C for 15 min. After the treatment, the sheet was air-cooled to room temperature.
[0047] Example 2
[0048] The difference between Example 2 and Example 1 is that the cold-rolled sheet is post-treated at 500° C. for 30 minutes; the remaining steps are the same as those in Example 1.
[0049] Example 3
[0050] The difference between Example 3 and Example 1 is that the cold-rolled sheet is post-treated at 500° C. for 60 minutes; the remaining steps are the same as those in Example 1.
[0051] Example 4
[0052] The difference between Example 4 and Example 1 is that the cold-rolled sheet is post-treated at 600° C. for 15 minutes; the remaining steps are the same as those in Example 1.
[0053] Example 5
[0054] The difference between Example 5 and Example 1 is that the cold-rolled sheet is post-treated at 600° C. for 30 minutes; the remaining steps are the same as those in Example 1.
[0055] Example 6
[0056] Weigh the corresponding amount of Co, Cr, Ni, and C raw materials with a purity of ≥99.9% on a balance, with an atomic percentage of 33.3:33.3:33.3:0.1, perform ultrasonic cleaning on the raw materials in anhydrous ethanol to remove impurities on the surface of the raw materials, and dry them for use. Mix the alloy raw materials evenly and put them into an induction melting furnace for melting under argon protection. The melting temperature is 1600±100℃, the heating rate is 300±100℃ / min, and the insulation time after the raw materials are melted is 15min; after insulation, pour the molten metal into a mold to form an ingot.
[0057] The ingot was placed in an annealing furnace at 1150°C for 240 minutes, and then air-cooled to room temperature. Then, the ingot at room temperature was heated to a hot rolling temperature of 1100°C by hot charging, with a heating rate of 200±100°C / min, a holding time of 15 minutes, a rolling deformation of 5% per pass, a total hot rolling deformation of about 20%, and a final rolling temperature of 1000±100°C to obtain a hot-rolled plate with a thickness of 8 mm; after hot rolling, it was air-cooled to room temperature.
[0058] The hot-rolled plate was annealed at 1150°C, with a heating rate of 10°C / min and a holding time of 10min. After the holding time, it was air-cooled to room temperature. The annealed plate was cold-rolled at room temperature, with a single rolling deformation of 2% and a total rolling deformation of 80%, to obtain a plate with a thickness of 1.2 mm.
[0059] The cold-rolled sheet was post-treated at 500°C for 15 min, and then air-cooled to room temperature.
[0060] Example 7
[0061] The difference between Example 7 and Example 6 is that the cold-rolled sheet is post-treated at 500° C. for 30 minutes, and the remaining steps are the same as those in Example 6.
[0062] Example 8
[0063] Weigh the corresponding amount of Co, Cr, Ni, C, and N raw materials with a purity of ≥99.9% on a balance, with an atomic percentage of 33.3:33.3:33.3:0.05:0.05, perform ultrasonic cleaning on the raw materials in anhydrous ethanol to remove impurities on the surface of the raw materials, and dry them for later use. After the alloy raw materials are mixed evenly, they are put into an induction melting furnace and melted under argon protection. The melting temperature is 1600±100°C, the heating rate is 300±100°C / min, and the insulation time after the raw materials are melted is 15min; after insulation, the molten metal is poured into a mold to form an ingot.
[0064] The ingot was placed in an annealing furnace at 1150°C for 240 minutes, and then air-cooled to room temperature. Then, the ingot at room temperature was heated to a hot rolling temperature of 1100°C by hot charging, with a heating rate of 200±100°C / min, a holding time of 15 minutes, a rolling deformation of 5% per pass, a total hot rolling deformation of about 40%, and a final rolling temperature of 1000±100°C to obtain a hot-rolled plate with a thickness of 8 mm; after hot rolling, it was air-cooled to room temperature.
[0065] The hot-rolled plate was annealed at 1150°C, with a heating rate of 10°C / min and a holding time of 10min. After the holding time, it was air-cooled to room temperature. The annealed plate was cold-rolled at room temperature, with a single rolling deformation of 2% and a total rolling deformation of 85%, to obtain a plate with a thickness of 1.2 mm.
[0066] The cold-rolled sheet was post-treated at 500°C for 15 min, and then air-cooled to room temperature.
[0067] Example 9
[0068] The difference between Example 9 and Example 8 is that the cold-rolled sheet is post-treated at 500° C. for 30 minutes, and the remaining steps are the same as those in Example 8.
[0069] Comparative Example 1
[0070] The difference between Comparative Example 1 and Example 1 is that the cold-rolled sheet is post-treated at 600° C. for 60 min; the remaining steps are the same as those in Example 1.
[0071] Comparative Example 2
[0072] The difference between Comparative Example 2 and Example 1 is that the cold-rolled sheet is post-treated at 700° C. for 15 minutes; the remaining steps are the same as those in Example 1.
[0073] Comparative Example 3
[0074] The difference between Comparative Example 3 and Example 1 is that the cold-rolled sheet is post-treated at 700° C. for 30 minutes; the remaining steps are the same as those in Example 1.
[0075] Comparative Example 4
[0076] The difference between Comparative Example 4 and Example 1 is that the cold-rolled sheet is post-treated at 700° C. for 60 min; the remaining steps are the same as those in Example 1.
[0077] Comparative Example 5
[0078] The difference between Comparative Example 5 and Example 1 is that the cold-rolled sheet is post-treated at 1150° C. for 10 min; the remaining steps are the same as those in Example 1.
[0079] test
[0080] The tensile strength of the samples prepared in Examples 1-9 and Comparative Examples 1-5 was tested by a conventional test method in the art, which will not be described in detail here. The test data is shown in Table 1.
[0081] Table 1 Tensile strength and strength increment data of alloys of Examples and Comparative Examples
[0082]
[0083]
[0084] Combining Table 1 and Figure 1 It can be seen that the grain boundary relaxation treatment of cold rolled sheet at 500℃ for 15min can effectively improve the tensile strength of the alloy material, indicating that in this process, excessive grain boundary dislocations are eliminated, the nucleation sites of dislocation sources are reduced, and the grain boundaries are transformed into low-energy states. Due to the reduction in the number of dislocation sources, the critical shear stress required for dislocation movement increases, which is manifested as an increase in alloy strength. Figure 2 and Figure 3 It can be clearly seen that after low-temperature grain boundary relaxation treatment, the excess dislocations introduced at the grain boundaries due to cold rolling are reduced, which will increase the shear stress required for dislocation movement and improve the strength of the alloy.
[0085] By comparing the test data of Examples 1-5 in Table 1, it can be seen that at 500-600°C, the tensile strength of the alloy can be increased by subjecting the cold-rolled sheet to grain boundary relaxation treatment. Specifically, in this process, the structure can undergo a partial recrystallization process, and the recrystallized structure has a lower dislocation density and better plasticity. Therefore, the coordinated effect of the cold-rolled deformed structure with high dislocation density and high strength and the recrystallized structure with low dislocation density and high plasticity can effectively improve the strength and plasticity of the alloy steel, breaking through the inverted relationship between the strength and plasticity of the alloy.
[0086] Furthermore, the longer the treatment time at 500°C, the more conducive it is to improving the tensile strength of the alloy; the longer the treatment time at 600°C, the lower the tensile strength of the alloy. This shows that high-temperature and long-term heat treatment is not conducive to improving the tensile strength of the alloy. Compared with the test data of Comparative Examples 1-5, where Comparative Example 1 extends the treatment time relative to Example 5, the tensile strength of its alloy drops sharply, and is lower than the tensile strength of the cold-rolled sheet before treatment. Comparative Examples 2-4 use 700°C to heat treat the cold-rolled sheet, and the tensile strength of the alloy after treatment is lower than that of Comparative Example 1. This shows that as the treatment temperature and treatment time of the cold-rolled sheet increase, the alloy grains grow significantly, the nanoscale relaxed grain boundaries disappear, and the tensile strength of the alloy decreases.
[0087] Comparing the test data of Examples 6-9 in Table 1, it can be seen that Co x Cr y Ni z -M a -N b The multi-component system can also improve the tensile strength of the alloy by subjecting the grain boundary to relaxation treatment at 500-600°C for 15-60 minutes. x Cr y Ni z Adding appropriate amounts of C and N to the ternary system and optimizing the composition can reduce the area of defect formation and affect the grain boundary bonding strength of the alloy to a certain extent, thereby improving the strength of the alloy.
[0088] Combining Table 1 and Figure 4 It can be seen that after the cold-rolled sheet is subjected to high-temperature heat treatment at 1150°C, the tensile strength of the alloy drops sharply, with a drop of 48%. This shows that when the cold-rolled sheet is subjected to high-temperature heat treatment, the recrystallized grains are large, the fine grain strengthening in the alloy is weak, and the critical shear stress of the alloy material is small, which is manifested as low alloy strength.
[0089] Compared with the prior art, the beneficial effects of the present invention are:
[0090] (1) Provide a Co x Cr y Niz -M a -N b Multi-element system, with Co, Cr, and Ni as the main components, simple components, relatively stable physical and chemical properties of the alloy, easy to control and optimize, C, P, O or N, M and N as added elements, can affect the grain boundary bonding strength of the alloy to a certain extent, and can prepare high-strength medium-entropy alloys with nanoscale relaxed grain boundaries, and the tensile strength of the alloy is 1.6-1.9GPa;
[0091] (2) Provide a method for preparing a high-strength medium-entropy alloy, which has a simple and efficient process flow and can be easily implemented based on the existing plate rolling production process, avoiding dependence on precision equipment and complex processes, and is conducive to large-scale application in industrial production;
[0092] (3) By performing grain boundary relaxation treatment at a lower temperature, the excessive dislocations introduced by cold rolling at the grain boundary are eliminated, and the grain boundary is transformed into a low-energy state. As the number of dislocation sources decreases, the critical shear stress required for dislocation movement increases, which is manifested as an increase in alloy strength.
[0093] (4) Based on the cold rolling process widely used in industrial production, the strength of the material can be significantly improved through low-temperature and short-term grain boundary relaxation treatment, which can reduce energy consumption and production costs, and has high economic benefits and application prospects.
[0094] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.
Claims
1. A method for preparing a high-strength medium-entropy alloy with nanoscale relaxed grain boundaries, characterized in that: The steps include: S1, smelting: weigh raw materials according to proportion, mix them evenly, and then smelt them under argon protection to obtain an ingot; S2, hot rolling: the ingot is homogenized, then hot rolled to obtain a hot-rolled plate, and then cooled to room temperature; S3, annealing and cold rolling: annealing the hot-rolled sheet and then cold-rolling it to obtain a cold-rolled sheet; S4, grain boundary relaxation: the cold rolled sheet is heated to 500-600°C for grain boundary relaxation treatment for 15-60 min. After the grain boundary relaxation treatment, the sheet is air-cooled to room temperature to obtain a high-strength medium-entropy alloy.
2. The method for preparing a high-strength medium-entropy alloy having nanoscale relaxed grain boundaries according to claim 1, characterized in that: In step S2, the hot rolling treatment adopts a hot charging method, the ingot at room temperature is heated to a hot rolling temperature of 1100±50°C, the heating rate is 100-300°C / min, the holding time is 15-30min, the rolling deformation amount of each pass is 5%-10%, and the total hot rolling deformation amount is 20%-40%; the final rolling temperature is 900-1100°C, and a hot-rolled plate with a thickness of 7-10mm is obtained; after hot rolling, it is air-cooled to room temperature.
3. The method for preparing a high-strength medium-entropy alloy having nanoscale relaxed grain boundaries according to claim 2, characterized in that: In step S2, the homogenization step is: placing the ingot in an annealing furnace at 1150±50°C for 200-240 minutes, taking it out and air-cooling it to room temperature.
4. A method for preparing a high-strength medium-entropy alloy with nanoscale relaxed grain boundaries according to claim 1, characterized in that: In step S3, the annealing treatment temperature is 1150±50°C, the heating rate is 5-15°C / min, the insulation time is 5-30min, and after the insulation is completed, the mixture is air-cooled to room temperature.
5. A method for preparing a high-strength medium-entropy alloy having nanoscale relaxed grain boundaries according to claim 4, characterized in that: In step S3, the cold rolling process has a single rolling deformation of 2% to 5%, a total rolling deformation of 80% to 85%, and a plate with a thickness of 1.0 to 1.5 mm is obtained.
6. A high-strength medium-entropy alloy having nanoscale relaxed grain boundaries prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The structural formula is Co x Cr y Ni z -M a -N b , wherein x, y, z, a, and b are all atomic percentages, and x+y+z+a+b=100%.
7. A high-strength medium-entropy alloy with nanoscale relaxed grain boundaries according to claim 6, characterized in that: x=25~35%, y=25~35%, z=25~35%.
8. The high-strength medium-entropy alloy with nanoscale relaxed grain boundaries according to claim 6, characterized in that: M and N may be the same or different and may be selected from C, P, O or N.
9. The high-strength medium-entropy alloy with nanoscale relaxed grain boundaries according to claim 6, characterized in that: The matrix structure of the high-strength medium-entropy alloy is dislocation cells with a size of 100 to 500 nm.
10. The high-strength medium-entropy alloy with nanoscale relaxed grain boundaries according to claim 9, characterized in that: The tensile strength of the high-strength medium-entropy alloy is 1.6 to 1.9 GPa.
Citation Information
Patent Citations
Preparation method of medium-entropy alloy with tensile strength of 1. 5 GPa
CN110273095A
High-strength high-plasticity wear-resistant high-entropy alloy and preparation method thereof
CN110499451A
Preparation method of high-strength and high-plasticity VCoNi medium-entropy alloy at low temperature
CN117025992A